Common fixed points in Chebyshev center for a semigroup of isometry mappings - Abhishek, Sharma; Rajesh, Sankara Narayanan (Topological Methods in Nonlinear Analysis, 2025)
In this article, we prove that if K is a nonempty weakly compact convex set having the normal structure in a Banach space B and F is a left reversible semitopological semigroup of isometry mappings from K into itself, then there exists a point in C(K) which is fixed by every member in F. This gives an affirmative answer to a question raised by Lim et al.